Analisis Karakteristik Pohon dan Sarang Orangutan Sumatera (Pongo abelii) di Bukit Lawang Kabupaten Langkat (Analysis of the Trees and Nest Characteristics of Sumatran Orangutan (Pongo abelii) in Bukit Lawang, Langkat District) - Muhammad Rifai; Pindi Patana; Yunasfi Yunasfi (Peronema Forestry Science Journal, 2013)
Research on "Analysis of the Trees and Nest Characteristics of Sumatran Orangutan (Pongo abelii) in Bukit Lawang Langkat District" was conducted in July until September 2012 at Pusat Pengamatan Orangutan Sumatera (PPOS) in Bukit Lawang, Bahorok, Langkat District. This study aims to investigate the characteristics of the nest tree and Sumatran Orangutan (Pongo abelii) based on age level and gender. Research method used line transect and focal animal sampling. Some characteristics of the Orangutans trees most often found in meranti trees (Shorea sp.) as Orangutans nest and feed, with hight 20-25 m, diameter 20-30 cm, branch pattern is adjacent and type of canofy is spherical, nest high 16-25 m. The position of the nest is most commonly found nesting in position III and nest type is B. There are differences and similarities between Orangutan who were subjected to experiments in determining the type of nest trees, nest trees high, nest trees diameter, nest high and position of nest. Keyword: Nest, Pongo abelii, Shorea sp., Sumateran Orangutans Trees and nest characteristic. Analisis Karakteristik Pohon dan Sarang Orangutan Sumatera (Pongo abelii) di Bukit Lawang Kabupaten Langkat Analysis of the Trees and Nest Characteristics of Sumatran Orangutan (Pongo abelii) in Bukit Lawang, Langkat District